Evaluation of behavioral outcomes in children 1 year after epilepsy surgery. (20th August 2015) - Law, Nicole; Kerr, Elizabeth; Smith, Mary Lou
Summary Objective Children with epilepsy have elevated rates of behavior problems. Research findings on the impact of epilepsy surgery on children's behavior have been mixed, with some studies showing improvements in behavior 3 to 18 months after surgery and other studies finding no change within this time interval. We examined behavior in a large surgical sample and in a nonsurgical comparison group. We also examined for potential effects of epilepsy‐related and cognitive/linguistic variables. Methods Behavior was assessed by parent report in 147 children who underwent epilepsy surgery and 40 children who did not, using the Child Behavior Checklist (CBCL). For the surgical group, the CBCL was completed prior to surgery (baseline) and approximately 1 year after surgery (follow‐up); ratings of the nonsurgical group were also conducted twice, at comparable intervals. Results At baseline, the groups did not differ on age, sex, age at seizure onset, antiepileptic drugs (AEDs), or intelligence quotient (IQ). Baseline Social and Attention Problems were higher in the nonsurgical group. At follow‐up, 65% of the surgical group and 20% of the nonsurgical group were seizure‐free. Behavioral change was not related to surgical status or seizure outcome. Children with temporal lobe seizure focus had more Externalizing Behaviors compared to those with frontal or multilobar foci. Attention was poorer in children who underwent frontal lobe excisions relative to temporal or multilobar excisions. Baseline IQ did not predict behavioral change. Significance Our results suggest that surgery and seizure outcome do not affect behavior in the first year following surgery; it may be the abnormal neural substrate and not seizure control that influences behavior in children with epilepsy. If changes are to occur due to seizure freedom, they may require a longer time to emerge. Some behaviors may be resistant to change in children with epilepsy or may require even longer intervals for improvement.